The Efficacy of Combined Exosome (Exodew) and Microneedling Treatment for Facial Pore Reduction and Skin Texture Improvement - Jovian Wan, MBChB; Song Eun Yoon, MD; Kyu-Ho Yi, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Enlarged facial pores are a common aesthetic concern that worsens with age due to increased sebum production, reduced skin elasticity, and photoaging. Although microneedling is known to stimulate collagen production, the combined use of stem cell–derived exosome therapy for pore reduction has not been thoroughly investigated. Methods:. A case series was conducted at a private aesthetic clinic between January and June 2024. Three patients (1 man and 2 women; 32–55 y of age; Fitzpatrick skin type IV) underwent 3 sessions of microneedling combined with topical exosome application (Exodew, Hyundae Meditech) at 4-week intervals. Standardized photographs were obtained at baseline and posttreatment. Clinical outcomes were evaluated using the Global Aesthetic Improvement Scale by 2 independent dermatologists and patient satisfaction scores at 12 and 22 weeks. Results:. All patients exhibited visible reductions in pore size and improvements in skin texture and overall appearance. Global Aesthetic Improvement Scale scores ranged from 4 to 5, indicating “very much improved” outcomes. Patient satisfaction was high at both 12- and 22-week follow-ups. No adverse events were reported, and improvements were sustained through week 22. Conclusions:. Microneedling combined with stem cell–derived exosome therapy seems to be a safe and effective treatment for facial pore reduction and skin texture enhancement. Larger, controlled studies are needed to confirm these preliminary results.